# Math

posted by .

For the equation 2x 3 - 11x 2 + 12x + 9 = 0, the root 3 has a multiplicity of _____.

• Math -

since we know 3 is a roots, x-3 must be a factor, so

2x^3 - 11x^2 + 12x + 9
= (x-3)(2x^2 - 5x - 3)
= (x-3)(x-3)(2x+1)

so .....

## Similar Questions

1. ### algebra

Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6 12x-11x=6 1x=6 x=6/1 x=6 Yes, that is correct
2. ### math

I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=0 x=6 Can someone show me the process of checking it?
3. ### Algebra

Find all of the zeros of the polynomial function and state the multiplicity of each. f (x) = (x^2 – 16)^2 A. – 4 with multiplicity 2 and 4 with multiplicity 2 B. – 4i with multiplicity 2 and 4i with multiplicity 2 C. 4 with multiplicity …
4. ### Algebra

Please help. Having a hard time with this. Find all of the zeros of the polynomial function and state the multiplicity of each. f (x) = (x^2 – 16)^2 A. – 4 with multiplicity 2 and 4 with multiplicity 2 B. – 4i with multiplicity …
5. ### Algebra

Find all of the zeros of the polynomial function and state the multiplicity of each. f (x) = (x^2 – 16)^2 A. – 4 with multiplicity 2 and 4 with multiplicity 2 B. – 4i with multiplicity 2 and 4i with multiplicity 2 C. 4 with multiplicity …
6. ### calculus

Using a graphing utility, graph and approximate the zeros and their multiplicity. A.x=0,multiplicity 2;x=7,multiplicity 3 B. x=0,multiplicity 2; x=7,multiplicity 1; x=-7, multiplicity 2 C. x=0,multiplicity 3;x=0,multiplicity 2 D.x=0,multiplicity …
7. ### algebra

find a third degree polynomial equation with coefficients that has roots -4 and 6+i possible answers x^3-8x^2-11x+148=0 x^3-8x^2-12x+37=0 x^3-12x^2+37x=0 x^3-8x^2-11x=0
8. ### precalc

For the equation 2x 3 - 11x 2 + 12x + 9 = 0, the root 3 has a multiplicity of _____.
9. ### Algebra 1b!

1. Find the excluded value of x for the polynomomial expression 4x/6 a. 6 b. -6 c. 1/6 d. -1/6 2. Simplifly 3-2x/7 + 4x+5/7 a. 2x+8/14 b. 2x+8/7 <--- c. x+1/7 d. 2x+2/7 3. Simplify 6ab^6/4a^7b^10 * a^3b^4/2a^7b^6 a. 7x/8 - 2x/8 …